Politik Pembangunan Islam terhadap Model Kota Madani Banda Aceh - Mau lida Ulfa; Warjio Lemane (Politeia: Jurnal Ilmu Politik, 2018)
This study is about the development of political Islam against a model city of madani in Banda Aceh. The focus of this study discusses the background and the concept model of the city of Banda Aceh and  programs and also the challenges. The findings of this study, among others, there are three important points. First, pemko Banda Aceh namely the Mayor and Vice Mayor who initiated the idea of the model of the city of Banda Aceh, where madani concept refers to what the Prophet had done in Madinah. Second, the political actors who involved in order to make the program run attempts to remain based on Islamic Shari’a. Third, the political actors still have constraints and should still be sought in order to realize Banda Aceh as a model of madani city. The method used is descriptive method.